Effect of anisotropy on the thermal volume changes of the Callovo–Oxfordian claystone. Issue 1 (2nd December 2019) - Braun, P.; Delage, P; Ghabezloo, S.; Sulem, J.; Conil, N.
Abstract : An accurate monitoring of axial and radial thermal strains of specimens of the Callovo–Oxfordian claystone, heated under constant confining stress conditions close to that prevailing in the Bure Underground Research Laboratory at 490 m depth, evidenced a particular behavioural feature. The effect of the transverse isotropy of the claystone on thermal strains was not only confirmed, but it was also shown that the thermo-elasto-plastic overall volumetric response was mainly due to the axial response, in which some influence of the adsorbed water is suspected. Conversely, the reversible radial response observed along a temperature cycle could be modelled through a simple homogenisation method that confirmed that it was governed by the thermo-elastic expansion/contraction response of the constitutive minerals. Hence, the simultaneous occurrence of elastic thermal radial strains and elasto-plastic thermal axial strains was evidenced.